The global economy and the euro area: Weak international trade, robust domestic demand - Claus Michelsen; Guido Baldi; Geraldine Dany-Knedlik; Hella Engerer; Stefan Gebauer; Malte Rieth (DIW Weekly Report, 2019)
The current global economic environment remains harsh. Global growth rates stagnated in the fourth quarter of 2018, particularly affected by foreign trade. DIW Berlin's forecast indicates global economic growth of 3.7 percent for 2019 and 3.6 percent for 2020. Positive stimuli are expected from catch-up effects (in the European automobile industry, for example) and the continued positive development on the labor markets, which will support consumption. However, the outlook for international trade is dominated by trade conflicts, political uncertainties, and a weaker Chinese economy. Although the trade conflict between the USA and China is beginning to ease, there are signs of a dispute between the USA and the European Union over EU automobile and car part exports to the USA. In Europe, the possibility of a no-deal Brexit and the political situation in Italy are causing uncertainty. Against this backdrop, monetary policy is likely to be expansionary in the forecast period.
Keywords: E32; E66; F01; 330; business cycle forecast; ecoomic outlook